Immunohistochemical Characterization of 120 Testicular Sex Cord-Stromal Tumors With an Emphasis on the Diagnostic Utility of SOX9, FOXL2, and SF-1. (October 2021) - Lau, Hubert D.; Kao, Chia-Sui; Williamson, Sean R.; Cheng, Liang; Ulbright, Thomas M.; Idrees, Muhammad T.
Abstract : Sex cord-stromal tumors (SCSTs) account for the second most common category of testicular neoplasms and include several entities that may show overlapping morphologies and present diagnostic challenges. We analyzed a cohort of 120 testicular SCSTs and investigated the diagnostic utility of SRY-box transcription factor 9 (SOX9), forkhead box protein L2 (FOXL2), and steroidogenic factor 1 (SF-1) immunohistochemical stains. The results were compared with the more commonly used SCST markers, inhibin α, calretinin, and Wilms' tumor 1 (WT1). SF-1 was overall the most sensitive stain (91%), followed by inhibin α (70%), calretinin (52%), FOXL2 (50%), SOX9 (47%), and WT1 (37%), but sensitivities varied by tumor type. SOX9 and calretinin were more commonly positive in sex cord elements versus stromal elements (62% vs. 27% and 47% vs. 9%, respectively), whereas FOXL2 was more commonly positive in stromal elements versus sex cord elements (100% vs. 55%) when excluding Leydig cell tumors from the stromal category. Although no individual stain was diagnostically specific, some immunophenotypic patterns were noted that may help in the subclassification of SCSTs. We conclude that SOX9, FOXL2, and SF-1 are useful immunohistochemical stains for confirming sex cord-stromal differentiation in testicular tumors and provide increased sensitivity as well as additional diagnostic information, especially when combined with the more commonly used inhibin α, calretinin, and WT1 immunostains. Although morphology is paramount for subclassification of SCSTs, knowledge of certain immunohistochemical patterns may be helpful for diagnostically challenging cases.